Deciphering Regulatory Networks Governing Seedling Emergence in Deep-Sown Direct-Seeded Rice Cultivation - Jasneet Singh; Nitika Sandhu; Aman Kumar; Om Prakash Raigar; Sutej Bains; Gaurav Augustine; Muskan Gupta; Ekta Kharche; Anu Kalia; Navtej Singh Bains; Arvind Kumar (Rice)
Abstract The rise of direct-seeded rice cultivation as a suitable alternative to transplanted puddled rice depends on developing genotypes with high seedling emergence under deep sown conditions. Two rice genotypes (IRGC 128442 and PR126) were screened for contrasting seedling emergence and subjected to high-throughput RNA sequencing under varying sowing depths (4 cm and 10 cm) and time intervals (5, 10, and 15 days after sowing). On average, a total of 2702 differentially expressed genes were identified across twelve inter- and intra-genotypic pairwise differential expression analyses, with a false discovery rate ≤ 0.05 and log2 fold change ≥ ± 2. The DEGs specifically showing differential expression under deep-sowing stress were prioritized and further refined based on their corresponding gene ontology terms, gene set enrichment analysis and KEGG and plant reactome pathway. From this pool of DEGs, 24 genes were validated using qRT-PCR. Among these, two genes (LOC_Os04g51460 and LOC_Os02g45450) contribute to cell wall remodelling and membrane stability, while three genes (LOC_Os04g48484, LOC_Os06g04399, and LOC_Os07g15440) play key roles in mitigating abiotic stress. Transcriptional regulators (LOC_Os06g33940 and LOC_Os01g45730) drive stress responses and growth. Notably, high fold changes in LOC_Os03g22720 and LOC_Os07g01960 underscore their importance in early stress responses and metabolic adjustments. The transcriptome analysis also highlighted the role of 29 heat shock proteins in response to deep sowing stress. Differential expression of key components in the abscisic acid (ABA)-mediated signalling pathway such as OsABI5 (LOC_Os01g64000), phosphatase 2C-like (PP2C) (LOC_Os09g15670) and OsPYL (LOC_Os06g36670) indicated downregulation of ABA signalling in the genotype IRGC 128442. Additionally, a role for miRNA-mediated regulation of auxin response factors was hypothesized in seedling emergence regulation. The study brings us closer to understanding the genetic control of seedling emergence under deep sown conditions. Functional validation of the key candidate genes and pathways could provide new targets for genetic improvement, potentially contributing to the development of rice cultivars optimized for direct-seeded rice cultivation.